Effect of a CNS-Sensitive Anticholinesterase Methane Sulfonyl Fluoride on Hippocampal Acetylcholine Release in Freely Moving Rats - Tamotsu Imanishi; Muhammad Mubarak Hossain; Tadahiko Suzuki; Ping Xu; Itaru Sato; Haruo Kobayashi (Advances in Pharmacological Sciences, 2012)
Anticholinesterases (antiChEs) are used to treat Alzheimer’s disease. The comparative effects of two antiChEs, methanesulfonyl fluoride (MSF) and donepezil, on the extracellular levels of ACh in the hippocampus were investigated by in vivo microdialysis in freely moving rats. MSF at 1 and 2 mg/kg produced a dose-dependent increase in ACh efflux from 10 min to at least 3 hrs after injection. At 2 mg/kg, the increase was still present at 24 hr. Donepezil at 1 mg/kg showed a similar but smaller effect, and, paradoxically, 2 mg/kg showed no consistent effect. MSF at 1 and 2 mg/kg decreased acetylcholinesterase activity in the hippocampus to 54.8 and 20.1% of control, respectively. These results suggest that MSF is a suitable candidate for the treatment of Alzheimer’s disease.